Patterns of myeloarchitecture in lower limb amputees: an MRI study - Hashim, Eyesha; Rowley, Christopher D.; Grad, Sharon; Bock, Nicholas A. (Frontiers in Neuroscience, 2015)
Functional studies of cortical plasticity in humans suggest that the motor cortex reorganizes when the descending motor output pathway is disrupted as a result of limb amputation. The question thus arises if the underlying anatomical organization of the motor cortex is also altered in limb amputation. Owing to challenges involved in imaging the thin cerebral cortex in vivo, there is limited data available on the anatomical or morphological plasticity of the motor cortex in amputation. In this paper, we study the morphology of the primary motor cortex in four lower limb amputees with 37 or more years of amputation and four age and gender-matched controls using 0.7 mm isotropic, T1-weighted MRI optimized to produce enhanced intracortical contrast based on myelin content. We segment the cortex into myelinated and unmyelinated gray matter. We determine the myelinated thickness which is the thickness of the well-myelinated tissue in the deeper layers of the cortex. We compare the bilateral differences in the myelinated thickness between amputees and controls. We also compare bilateral differences in cortical thickness between the two groups. Our measurements show no statistically significant difference between the amputees and controls in the myelinated thickness and in cortical thickness, in the region of the primary motor cortex representing the lower leg.